Yield evaluation of curly chili lines in three lowland locations - MUHAMAD SYUKUR; ZULFIKAR DAMARALAM SAHID; SOBIR SOBIR; AWANG MAHARIJAYA; ARYA WIDURA RITONGA; YUNANDRA YUNANDRA; SULASSIH SULASSIH; MUHAMMAD RIDHA ALFARABI ISTIQLAL; ABDUL HAKIM; YUDIWANTI WAHYU; TOBIAS MONIZ VICENTE; MUKHLISIN MUKHLISIN; KARLIN AGUSTINA; YURSIDA YURSIDA; KUNCI MUSLIMIN; SITI HAFSAH; NURA NURA; ANDRY SETYAWAN (Society for Indonesian Biodiversity, 2022)
Abstract. Syukur M, Sahid ZD, Sobir, Maharijaya A, Ritonga AW, Yunandra, Sulassih, Istiqlal MRA, Hakim A, Wahyu Y, Vicente TM, Mukhlisin, Agustina K, Yursida, Muslimin K, Hafsah S, Nura, Setyawan A. 2022. Yield evaluation of curly chili lines in three lowland locations.Biodiversitas 23: 3219-3223. Yield evaluation of curly chili lines in three lowland locations. Increased consumption of spicy food is the latest trend in the 21st century. Curly chili as a type of chili that has a spiciness that is acceptable to the community is needed to meet consumer needs. This study aims to identify the growth, fruit, and yield components of several genotypes of curly chili. The study was conducted in multi-location at four planting sites. Each location used a randomized complete block design (RCBD) with three replications. Each replication used ten sample plants. Neno IPB as a chili variety produced by breeding has a faster flowering and harvesting time than all other genotypes. In addition, the productivity of Neno IPB was high and consistent in all cultivation locations. The results of the pheatmap analysis show that Neno IPB was one group with commercial varieties (Laris and Kastilo F1). A significant positive correlation based on Pearson's analysis was shown in the combination of flowering time-harvesting time, fruit length-fruit weight, and fruit weight per plant-total fruit per plant-productivity. However, flowering time-harvesting time-fruit weight per plant showed a significant negative correlation.